North‐South Negotiations about Financing for Development: State, Society and Market in the Global Age. Issue 3 (14th April 2018) - Freeman, Dena
Abstract: In contemporary global politics different actors seek to create contrasting world orders through the existing mechanisms of global deliberation and policy making. This article draws on the anthropology of policy to elucidate some of the different potential world orders that are being discussed today. Developing the concept of 'policy vision', the article seeks to bring into focus the different policy visions currently being proposed by the countries of the North and those of the South in global policy negotiations at the United Nations. To do this it critically scrutinizes the divergent North‐South positions in the negotiations leading up to the 2015 UN Financing for Development conference in Addis Ababa and draws out their divergent visions of alternative world orders. The conclusion sets these alternative world orders within Dani Rodrik's 'political trilemma of the global economy' and considers their implications for the future of state, society and market in the global age. Abstract : In many respects the North – South debate in the FFD process seems to be very similar to right – left political debates that take place at national level. The policy vision of the North is right wing neoliberal while that of the South promotes a more left wing vision akin to social democracy. But it is more complex than this because within each policy vision there are also contrasting visions about the relative importance of the national and the global, and in particular about how states and markets should function at these two levels.